University Guide using Speech Recognition and Computer Vision - Anthony Kosasi; Nur Hadisukmana; Rosalina Rosalina; R.B. Wahyu; Budi Sulistyo; Yuyu Wahyu (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2017)
Education is an important factor inside mankind’s existence. However, choosing a great and promising place to learn is a very hard thing to do, especially for senior high school student who want to continue their education into the university. There are a lot of universities around us and a lot of major or concentration that we must choose before entering a university Considering this issue, Some application will be developed and the application will help people in understanding some majors those are available and help people to know about some universities in Indonesia whether about vision, mission, curriculum, etc. This application will not be a boring information application that provides information in text and let user read it. This is rather an attractive application that will tell some information about each major in speech and also give information about each university when user scan the university logo with computer vision. Not only that, after user scans the university logo, video profile of the university will be played and then user can pause, stops or plays the video also by using speech. Some additional feature like migration into major field and website link will also be provided.